Living with Ulcerative Colitis Study (LUCY) in England: a retrospective study evaluating healthcare resource utilisation and direct healthcare costs of postoperative care in ulcerative colitis - Joseph C Cappelleri; Matthew J Brookes; Natalie Bohm; John Waller; Irene Modesto; Marco D DiBonaventura; Ruth Mokgokong; Danielle Bargo (BMJ Open Gastroenterology)
Objective Ulcerative colitis (UC) is a lifelong, relapsing-remitting disease. Patients non-responsive to pharmacological treatment may require a colectomy. We estimated pre-colectomy and post-colectomy healthcare resource utilisation (HCRU) and costs in England.Design/Method A retrospective, longitudinal cohort study indexing adult patients with UC undergoing colectomy (2009–2015), using linked Clinical Practice Research Datalink/Hospital Episode Statistics data, was conducted. HCRU, healthcare costs and pharmacological treatments were evaluated during 12 months prior to and including colectomy (baseline) and 24 months post-colectomy (follow-up; F-U), comparing baseline/F-U, emergency/elective colectomy and subtotal/full colectomy using descriptive statistics and paired/unpaired tests.Results 249 patients from 26 165 identified were analysed including 145 (58%) elective and 184 (74%) full colectomies. Number/cost of general practitioner consultations increased post-colectomy (p<0.001), and then decreased at 13–24 months (p<0.05). From baseline to F-U, the number of outpatient visits, number/cost of hospitalisations and total direct healthcare costs decreased (all p<0.01). Postoperative HCRU was similar between elective and emergency colectomies, except for the costs of colectomy-related hospitalisations and medication, which were lower in the elective group (p<0.05). Postoperative costs were higher for subtotal versus full colectomies (p<0.001). At 1–12 month F-U, 30%, 19% and 5% of patients received aminosalicylates, steroids and immunosuppressants, respectively.Conclusion HCRU/costs increased for primary care in the first year post-colectomy but decreased for secondary care, and varied according to the colectomy type. Ongoing and potentially unnecessary pharmacological therapy was seen in up to 30% of patients. These findings can inform patients and decision-makers of potential benefits and burdens of colectomy in UC.